The fragility of welcome – commentary to Gill - Jonathan Darling (Fennia: International Journal of Geography, 2018)
In this commentary, I take Nick Gill’s discussion of the ‘suppression of welcome’ and the politics of hospitality, as a starting point for reflection on how ‘cultures of welcome’ are produced. In exploring the work of those supporting asylum seekers and refugees in Sheffield, UK, I argue that welcome may encompass a range of practices, with varying levels of intention and recognition attached. Yet what draws these practices together are two factors, first, a positive engagement with difference that holds the potential to promote solidaristic, or at the very least non-violent, relations. And second, a fragility that means that welcome is always at risk of being suppressed or commandeered for other purposes. In considering the implications of the ‘suppression of welcome’, I argue for a focus on welcoming as a negotiated process that involves varying durations, demands and levels of commitment.